Involvement, participation and partnership: a review of the debate and reflections on the Irish context - Gunnigle, Patrick (Limerick, 2007)
"Employee participation and involvement may be broadly viewed as incorporating mechanisms designed to increase employee input into managerial decision-making, and is often viewed as the political democratisation of the workplace. In this field, commentators normally differentiate between direct and indirect forms of employee influence. This paper reviews the nature of direct and indirect (representative) participation and subsequently considers research evidence on the diffusion of these varying modes of employee influence in Ireland. We find that the different actors in industrial relations have particular preferences in terms of their desired approach. We further conclude that the prospects for high level 'strategic partnership' remain poor, especially in the multinational sector. There is, however, considerable evidence of employer initiatives to facilitate higher levels of direct employee involvement in operational decision making."